Risk factors for retinopathy of prematurity in six neonatal intensive care units in Beijing, China. Issue 3 (26th February 2008) - Chen, Y; Li, X-x; Yin, H; Gilbert, C; Liang, J-h; Jiang, Y-r; Zhao, M-w; ,
Abstract : Objective: Guidelines on oxygenation policies and on the prevention and treatment of retinopathy of prematurity (ROP) were issued by the Chinese Medical Association in 2004. This study was undertaken to determine the incidence of and risk factors for ROP among preterm infants in Beijing, the capital of China, after implementation of the guidelines. Methods: Neonates with birth weights (BW) ⩽2000 g or gestational age (GA) ⩽34 weeks admitted to the six largest neonatal intensive care units in Beijing during 2005 were enrolled. Ophthalmological examinations started 3–4 weeks after birth, and ROP was classified using the revised International Classification. Maternal and perinatal risk factors for type 1 ROP were analysed. Results: Retinopathy of prematurity was detected in 10.8% of 639 neonates who had complete eye examinations, 23 of whom (3.6%) developed type 1 ROP and were treated. The rate of ROP needing treatment has not declined since 2002. Logistic regression analysis indicated that low BW, apnoea >20 s, anaemia, hypoxic–ischaemic encephalopathy and placenta abruption were significantly associated with type 1 ROP. Conclusion: In Beijing, rates of ROP needing treatment are high, and affected babies are more mature than in NICUs in high-income countries. More needs to be done to prevent ROP through improved neonatal care.